Antimycobacterial ingredients from plants used in traditional medicine to treat Buruli ulcer. (December 2016) - Tsouh Fokou, Patrick Valere; Kissi-Twum, Abena Adomah; Yeboah-Manu, Dorothy; Appiah-Opong, Regina; Addo, Phyllis; Yamthe, Lauve Rachel Tchokouaha; Mfopa, Alvine Ngoutane; Boyom, Fabrice Fekam; Nyarko, Alexander Kwadwo
Abstract: Aim and objectives: Buruli ulcer (BU) is a neglected tropical disease caused by a mycobacteria, Mycobacterium ulcerans . The WHO recommended Rifampicin-Streptomycin combination side effects and poor compliance, leaves rural populations with no choice than to patronise indigenous remedies. This study is aimed at validating medicinal plants used in traditional medicine to treat BU by investigating the in vitro efficacy and safety as well as their composition in active molecules. Methods: A short report-based survey was used to identify medicinal plants used traditionally for BU treatment. Maceration of collected plant samples in methanol, hydroethanolic, ethanol, dichloromethane, and hexane, resulted in a total of 67 extracts assessed for antimycobacteria activity against Mycobacterium smegmatis and Mycobacterium ulcerans using the Resazurin Microtiter Assay. The cytotoxicity effect of promising extracts was assessed on normal human liver cells using the MTT assay. The bio-guided fractionation of the promising extracts led to the isolation of active compounds. Results: Majority of plants prepared as infusion, decoction, poultice, and macerate were administered topically. Significant antimycobacterial activity with MIC values ranging from 16 to 250 μg/mL was recorded against M. smegmatis (25 extracts) and M. ulcerans (17 extracts). 1 Most of antimycobacterial extracts showed no significant cytotoxicity against normal human hepatocytes. 1 The isolation guided by the biological activity revealed nine compounds with significant in vitro anti- M. ulcerans activity (MIC = 16–128 μg/mL). Conclusions: The results completed support the use these plants in the indigenous knowledge against BU. Further analyses of active principles might lead to new drug toe fight against BU.